Migration and Foreign Direct Investment: Education Matters - Masood Gheasi; Peter Nijkamp; Piet Rietveld (Tinbergen Institute, 2011)
The rapid growth in the foreign-born population in many high and middle-income countries in recent decades has prompted much research on the socio-economic determinants and impacts of immigration. This paper investigates the relationship between the stock of foreign population by nationality living in the UK and the bilateral volume of foreign direct investment (FDI), both inward FDI into the UK and outward FDI from the UK. This study contributes to the literature on the above-mentioned association between migration and FDI, by using the UK annual data from 2001 to 2007 for 22 countries on the inward volume of FDI and for 27 countries on the outward volume of FDI. Our study finds a significant and positive relationship between migration and outward FDI. This result also holds, if we correct for endogeneity by using an instrumental variable approach. If we then include the education level of migrants living in the UK, our results indicate that the more educ ated migrants from a certain country are, the stronger positive effect they have on FDI in both directions (inward and outward).
urn:NBN:nl:ui:31-1871/38525
Keywords: F22; P45; 330; foreign direct investment; immigration; gravity model; instrumental variable; Migranten; Bevölkerungsstruktur; Auslandsinvestition; Großbritannien